English Communication Competence of Nature Tourism Guides in Indonesia: Challenges, Needs, and Development Strategies - Morita Morita; Donny Hendry Fahsani; Mumuh Mulyana (Prodi Pariwisata dan LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Nature tourism is one of Indonesia’s most strategic tourism assets because the country offers diverse landscapes, biodiversity, marine resources, forests, mountains, waterfalls, national parks, geoparks, and rural ecotourism destinations. As international tourist mobility continues to recover and grow, the role of nature tourism guides becomes increasingly important. They are not only responsible for accompanying visitors but also for interpreting natural attractions, explaining ecological and cultural meanings, ensuring safety, mediating intercultural interaction, and representing the quality of Indonesian tourism services. In this context, English communication competence is a central professional requirement. However, many nature tourism guides still experience difficulties in using English effectively, especially when explaining biodiversity, giving safety instructions, responding to spontaneous questions, handling complaints, and communicating with tourists from different cultural backgrounds. This article aims to analyze the English communication competence of nature tourism guides in Indonesia, identify the main challenges they face, map their English training needs, and propose development strategies for strengthening their professional competence. Using a conceptual and literature-based approach, this article integrates perspectives from English for Specific Purposes, communicative competence, intercultural communication, tourism service quality, and sustainable tourism. The analysis suggests that the English competence required by nature tourism guides must go beyond general conversational ability. It should include functional guiding English, environmental interpretation, storytelling, intercultural sensitivity, safety communication, emergency communication, and digital communication. The article proposes an integrated development model consisting of needs-based curriculum design, field simulation, micro-guiding practice, mentoring, certification, digital learning, and collaboration among tourism offices, guide associations, universities, destination managers, and local communities. The study contributes to the discussion on tourism human resource development and offers practical recommendations for improving the competitiveness and sustainability of Indonesian nature tourism. Keywords: English communication competence; nature tourism guides; English for tourism; ecotourism; intercultural communication; Indonesia; sustainable tourism.